On Some Properties of New Paranormed Sequence Space of Nonabsolute Type - Vatan Karakaya; Necip Şimşek (Abstract and Applied Analysis)
We introduce some new generalized sequence space related to the space ℓ(𝑝). Furthermore we investigate some topological properties as the completeness, the isomorphism, and also we give some inclusion relations between this sequence space and some of the other sequence spaces. In addition, we compute 𝛼-, 𝛽-, and 𝛾-duals of this space and characterize certain matrix transformations on this sequence space.